2013
DOI: 10.1002/chem.201300689
|View full text |Cite
|
Sign up to set email alerts
|

How Is a Metabolic Intermediate Formed in the Mechanism‐Based Inactivation of Cytochrome P450 by Using 1,1‐Dimethylhydrazine: Hydrogen Abstraction or Nitrogen Oxidation?

Abstract: A precise understanding of the mechanism-based inactivation of cytochrome P450 enzymes (P450s) at the quantum mechanical level should allow more reliable predictions of drug-drug interactions than those currently available. Hydrazines are among the molecules that act as mechanism-based inactivators to terminate the function of P450s, which are essential heme enzymes responsible for drug metabolism in the human body. Despite its importance, the mechanism explaining how a metabolic intermediate (MI) is formed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 101 publications
5
42
1
Order By: Relevance
“…Rather, one must use quantum mechanical methods such as DFT. In recent years, several research groups have reported DFT studies of P450 MBI (de Visser et al, 2004; Rydberg and Olsen, 2011; Hirao et al, 2012, 2013a,b; Taxak et al, 2012, 2013a,b). …”
Section: Applications Of Dftmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, one must use quantum mechanical methods such as DFT. In recent years, several research groups have reported DFT studies of P450 MBI (de Visser et al, 2004; Rydberg and Olsen, 2011; Hirao et al, 2012, 2013a,b; Taxak et al, 2012, 2013a,b). …”
Section: Applications Of Dftmentioning
confidence: 99%
“…Hirao et al also studied the mechanism of metabolic-intermediate formation in the quasi-irreversible MBI of P450 caused by 1,1-dialkylhydrazine (or unsymmetrical dimethylhydrazine, UDMH) (Hirao et al, 2013a). For this MBI, hydrazine is converted to an aminonitrene metabolic intermediate, which in turn binds to the heme iron.…”
Section: Applications Of Dftmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of P450 enzymes, with oxidation mechanisms and inhibition has received particular attention [30][31][32][33][34][35][36]. Plant AOS and related atypical P450s in the prostaglandin H 2 to prostacyclin pathway have also been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…To describe such reactive processes computationally, one must resort to quantum chemistry. In recent years, quantum chemical studies of P450 MBI using density functional theory (DFT) have become increasingly prevalent [2429]. …”
Section: Introductionmentioning
confidence: 99%